2022
DOI: 10.1097/adm.0000000000001110
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-methods Evaluation of an Addiction/Cardiology Pilot Clinic With Contingency Management for Patients With Stimulant-associated Cardiomyopathy

Abstract: ObjectivesContingency management (CM) is one of the most effective treatments for stimulant use disorder but has not been leveraged for people with stimulant-associated cardiomyopathy (SA-CMP), a chronic health condition with significant morbidity and mortality. We aimed to determine the feasibility and acceptability of a multidisciplinary addiction/cardiology clinic with CM for patients with SA-CMP and to explore barriers and facilitators to engagement and recovery.MethodsWe recruited patients with a hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…While we did not have access to information related to long-term substance use prior to OHCA, previous studies have found an association between long-term stimulant use and cardiovascular pathology, including atherosclerosis and cardiomyopathy . The extent to which this underlying pathology further challenges resuscitation and outcomes in the setting of stimulant-only OHCA is unknown but may have implications for the timing and scope of preventive measures in this population …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…While we did not have access to information related to long-term substance use prior to OHCA, previous studies have found an association between long-term stimulant use and cardiovascular pathology, including atherosclerosis and cardiomyopathy . The extent to which this underlying pathology further challenges resuscitation and outcomes in the setting of stimulant-only OHCA is unknown but may have implications for the timing and scope of preventive measures in this population …”
Section: Discussionsupporting
confidence: 58%
“…30 The extent to which this underlying pathology further challenges resuscitation and outcomes in the setting of stimulant-only OHCA is unknown but may have implications for the timing and scope of preventive measures in this population. 31,32 We observed poorer outcomes among patients with OHCA with combined opioid and stimulant use. Despite similar EMS response and treatment profiles to other OD groups, this combined group was less likely to be alive at the end of EMS care and had lower survival to hospital discharge.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We are writing in response to the article “A mixed methods evaluation of an addiction/cardiology pilot clinic with contingency management for patients with stimulant-associated cardiomyopathy” published by Leyde et al 1 in December 2022. We want to share a similar contingency management (CM) feasibility pilot conducted among a vulnerable veteran patient population with stimulant-associated cardiomyopathy (SA-CMP).…”
mentioning
confidence: 99%
“…A multidisciplinary team designed to meet this population’s unique needs and deliver non-stigmatising, patient centred care is mandatory. This model has been shown to be highly effective in increasing engagement and clinic attendance while simultaneously reducing stimulant use and acute care utilisation 9. Meaningful progress necessitates that healthcare systems financially commit to novel care delivery approaches that support and encourage patient engagement and reduce methamphetamine use.…”
mentioning
confidence: 99%